Sleeping Giants Arise: Monitoring the Return of Three Changing-look Quasars to Their High States - Laura Duffy; Michael Eracleous; John J. Ruan; Qian Yang; Jessie C. Runnoe (The Astrophysical Journal)
Changing-look quasars (CLQs) challenge many models of the quasar central engine. Their extreme variability in both the continuum and broad emission-line fluxes on timescales on the order of years is difficult to explain. To investigate the cause of the observed transitions, we present new contemporaneous optical and X-ray observations of three faded CLQs as they return to a state of high optical luminosity. Two of these three remained in a quiescent state for more than 10 yr before returning to a new high state. We find that before, during, and after transition, the spectral energy distributions of all three follow predictions for quasars based on X-ray binary outbursts, suggesting that the underlying mechanism is likely a changing accretion rate causing changes in the accretion flow structure. In two of the three cases, the transition between the initial high and low state and the transition between the low and new high state took nearly identical amounts of time, on the order of hundreds of days. This transition timescale is a useful constraint on models of the accretion state changes. The behavior of the broad emission-line profiles suggests that the broad-line region structure is changing during the transition.